AktivitasKomunikasi Ibu dan Anak Saat Belajar Daring - Dini khaerunisa; Oji Kurniadi (UNISBA Press, 2022)
Abstract. At the beginning of 2020 the COVID-19 pandemic was endemic in many countries in the world, including Indonesia. The pandemic has had a broad secondary impact, the education of 80 million Indonesian children and youth has been disrupted, access to health services, nutrition, and protection has been greatly affected (UNICEF: 2021). The government's policy to prevent the spread of the COVID-19 virus has forced students and teaching staff as well as the entire academic community to carry out online teaching and learning activities. The role of a teacher in a school that is taken over by a mother makes it more difficult for children to work together to learn, Mothers also often have difficulties that often lead to giving birth with the child. It is important for mothers to know and apply appropriate communication to their children when studying at home. In order for parents to be able to carry out their functions properly, parents need to understand the level of child development, assess the growth and development of children and have a strong motivation to advance the growth and development of children (Anwar in Harmaini: 2013). This research uses a qualitative method with a case study approach. Data were collected by interview, observation, and documentation techniques. The results of this study are 1). Interpersonal communication between mothers and children in working mothers is not well established because they do not build interpersonal communication factors and do not meet the requirements for effective communication. While for mothers who do not work, interpersonal communication is established quite well because it builds interpersonal communication factors, but the communication is not effective enough because it does not meet the requirements for effective communication.; 2). Mother's style of speaking is relaxed to children when doing online learning, to mothers who work because of the lack of communication that makes the style of speech too relaxed, meaning that the relationship is closer but instead erodes respect. Meanwhile, for mothers who do not work, because they often communicate, the style of speaking between mothers and children is relaxed but still pays attention to politeness and courtesy; 3). The reasons mothers and children often fight during online learning include children's moods that are often not good because they are bored with online learning, the burden of mother's thoughts, mothers who do not understand children's learning materials, to children who yell when they are told. In the end, it is seen that the communication pattern of working mothers is a permissive communication pattern. Meanwhile, the communication pattern for mothers who do not work is a democratic communication pattern. Abstrak. Pada awal tahun 2020 pandemi covid-19 mewabah di banyak negara di dunia termasuk Indonesia. Pandemi memberikan dampak sekunder yang luas, pendidikan 80 Juta anak dan remaja Indonesia terganggu, akses layanan kesehatan, gizi, dan perlindungan terdampak begitu besar (UNICEF : 2021). Adanya kebijakan pemerintah atas upaya pencegahan penyebaran virus covid-19 memaksa para siswa dan tenaga pengajar serta seluruh civitas akademi untuk melangsukan kegiatan belajar mengajar secara daring. Peran seorang guru di Sekolah yang diambil alih oleh seorang Ibu menjadikan anak-anak cenderung lebih sulit diajak kerjasama untuk belajar, para Ibu pun sering kali kesulitan hingga sering kali menyebabkan pertengkaran dengan sang anak. Penting bagi para Ibu untuk mengetahui dan menerapkan komunikasi yang sesuai kepada sang anak ketika akan belajar di Rumah. Agar orang tua mampu melaksanakan fungsinya dengan baik maka orang tua perlu memahami tingkat perkembangan anak, menilai pertumbuhan dan perkembangan anak serta mempunyai motivasi yang kuat untuk memajukan pertumbuhan dan perkembangan anak (Anwar dalam Harmaini :2013). Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data dikumpulkan dengan teknik wawancara, observasi, dan dokumentasi. Hasil Penelitian ini adalah 1). Komunikasi antar pribadi Ibu dan anak pada Ibu bekerja tidak terjalin dengan baik karena tidak membangun faktor-faktor komunikasi antarpribadi serta tidak memenuhi syarat komunikasi effektif. Sedangkan pada Ibu tidak bekerja, komunikasi antarpribadi terjalin dengan cukup baik karena membangun faktor-faktor komunikasi antarpribadi, namun komunikasi yang dilakukan pun tidak cukup efektif karena tidak memenuhi syarat komunikasi efektif; 2). Gaya bicara Ibu santai pada anak saat melakukan pembelajaran daring, pada Ibu yang bekerja karena jarangnya bekomunikasi menjadikan gaya bicara terlalu santai, bermaksud agar hubungan lebih dekat namun malah mengikis rasa hormat. Sedangkan pada Ibu yang tidak bekerja, karena seering melakukan komunikasi gaya bicara Ibu dengan anak santai namun tetap memperhatikan sopan dan santun; 3). Alasan Ibu dan anak sering kali bertengkar saat pembelajaran daring diantaranya adalah mood anak yang sering kurang baik karena bosan belajar daring, banyaknya beban fikiran Ibu, Ibu yang Tidak mengerti materi pembelajaran anak, hingga anak yang mengeyel jika diberi tahu. Pada akhirnya terlihat bahwa pola komunikasi pada Ibu yang bekerja adalah pola komunikasi permisif. Sedangkan pola komunikasi pada Ibu yang tidak bekerja adalah pola komunikasi demokratis.